ANALISIS KELAYAKAN FINANSIAL PENGOLAHAN IKAN LELE MENJADI ABON IKAN LELE DI KECAMATAN MESTONG KABUPATEN MUARO JAMBI - Khairil Khairil; Emanauli Emanauli; Fenny Permata Sari; Nur Hasnah AR; Sispa Pebrian (Indonesian Journal of Agricultural Economics, 2023)
This study aims to determine the process of processing catfish into shredded catfish, as well as to determine the financial feasibility of processing catfish into catfish floss. Data obtained from secondary data and primary data. The method used in this research is descriptive and quantitative methods. Based on the results of the study, it showed that the financial analysis obtained by the BEP production volume was 37,980 packages per year and the BEP selling price was Rp. 26,974 / packaging. The NPV obtained is Rp. 249.335.495,16 (NPV > 0) so that this business is feasible to run. The IRR obtained was 36% with a payback period (PP) of 2.1 years and a Net B/C greater than one, namely 1.07. This means that the business of processing catfish becamess shredded catfish is feasible to run. The sensitivity analysis of the catfish shredded business has the ability to tolerate a decrease in revenue of 80%, for the highest price tolerance it reaches 90% and can be carried out up to a price reduction of 90%.